Cotton yield and boron dynamics affected by cover crops and boron fertilization in a tropical sandy soil - Cordeiro, Luis Fernando dos Santos [UNESP]; Cordeiro, Carlos Felipe dos Santos [UNESP]; Ferrari, Samuel [UNESP] (Elsevier, 2022)
Cover crops may affect diversely boron (B) availability and cotton yield, especially in tropical sandy soils. In turn, B fertilizer rates required by cotton can be dependent on the use of cover crops. This study aimed to evaluate cotton yield, soil-plant B dynamics, and soil fertility as a function of cover crops (fallow, millet, black velvet bean, and millet+ black velvet bean) and B fertilization rates (0, 1, 2, 4, and 6 kg ha−1). The experiment was carried out at the field in two crop seasons (2019/2020 and 2020/2021), in Dracena, São Paulo State, Brazil. Cover crops increased cotton fiber yields by 47% compared to fallow soil (average two crops), as well as improved B cycling and soil fertility. Proper B rates increased cotton fiber yield by 18%. A maximum cotton fiber yield was reached at 4 kg B ha−1 (millet + black velvet bean), 2 kg B ha−1 (black velvet bean) in the 2020/2021 crop season, and 1 kg B ha−1 in the other system. Critical levels of leaf B ranged from 12 to 16 mg kg−1. Maximum B uptakes were 182 and 232 g B ha−1 in the first and second crop seasons, respectively. Boron application and cover crops increased B contents in the soil, but it was below 0.6 mg B dm−3 in the topsoil. When associated with B fertilization, cover crops, especially the intercropping between millet and black velvet bean, improved soil fertility, plant nutrition, and cotton fiber yields in the tropical sandy soil.
Keywords: Boron leaching; Boron uptake; Marginal areas; Organic matter; Soil fertility